A Reconfigurable and Evolvable Platform for Network Function Innovation - Jianhui Zhang; Tong Duan; Xiaohui Zhang; Yuxiang Hu (Dianxin kexue)
With the development of the internet, new network architectures and new protocols are emerging. But because of the the inflexible circuits of traditional network devices, the experiment and deployment of new functions are limited. To dealing with this problem, a reconfigurable and evolvable platform for network function innovation was proposed, which could adapt to the demand of network services by orchestrating functional modules in software plane. Then, configurable meta operation unit was used as data processing packet in hardware plane. Finally, the application prospect of the proposed innovation platform was given combined with two use cases.